Evaluation of larval toxicity, mode of action and chemical composition of citrus essential oils against Anopheles stephensi and Culexquinquefasciatus. (January 2022) - Sharma, Shivani; Loach, Neha; Gupta, Shweta; Mohan, Lalit
Abstract: Mosquitoes are the most significant insect vectors and are known for their community health prominences, which causes economic and social disturbances. Almost currently implemented strategies for mosquito control are based on synthetic insecticides, which have several toxic exposures to humans, animals and other non-targets as well as multiplied various environmental pollution. Hence, the mosquito larvicidal impact of essential oils of Citrus limetta (Musambi), C. limon (Lemon) and C. reticulata (Kinnow) was evaluated. The essential oils obtained through hydrodistillation and further characterized by phytochemical and GC-MS examinations. The larvicidal bioassay was performed according to the standard protocol of WHO, 2005 with slide modifications. The results indicated that alkaloids, terpenes, terpenoids, anthraquinones, flavonoids and tannins were present in the leaves and peels. d ‒Limonene, β‒Terpinene, Linalool, Citral, α‒Pinene β‒Caryophyllene, Terpinen‒4‒ol, γ‒Terpinene, 3‒Carene, Sylvestrene, β‒Ocimene, β‒Thujene, Citronellal, Sabinene and β‒Pinene were determined as major phytocompounds. Moreover, C. limetta was found as the most potent larvicide. The essential oil of leaves having LC50 and LC90 values 23.77 ± 3.45 and 81.07 ± 15.24 ppm and 35.12 ± 3.55 and 81.30 ± 10.79 ppm and in the case of peels 16.31 ± 3.50 and 77.60 ± 18.17 ppm and 29.20 ± 3.11 and 68.62 ± 9.03 ppm against Anopheles stephensi and Culex quinquefasciatus after 24 h, respectively. Therefore, they can be used as environmental friendly and cheap botanical mosquitocides. Graphical abstract: Image 1 Highlights: Larvicidal efficacy of essential oils isolated from Citrus leaves and peels against significant mosquito vectors. Citrus plants selected are economically and widely cultivated species and are waste products of juice industries. Phytochemical and GC-MS analysis were performed to show the presence of phytocompounds. Essential oils may have ability to cross the cell membrane of target organism as they have higher LogP values. Essential oils are biodegradable, eco-friendly and cost effective botanicals of larvicidal nature.